The Use of Different Weights and Resistances and their Effect on Bending the Muscles of the Lower Limbs and the Achievement of the Long Jump Contestants for Al Diwaniyah Clubs in Athletics - Karim Abdul Hussein Al-Jaber; Basma Abdul Hussein Shandal (Institute of Medico-legal Publications Pvt Ltd, 2021)
The research included several topics, where the two researchers touched on the introduction and importance of the research in the first section, as all sources and research confirm the importance of using weights in training programs because of their importance in developing working muscles, especially in activities of jumping and jumping and thus reflected positively on achievement, as for the problem of research lies inferior The level of achievement for the effectiveness of the long jump, especially in the local championships, due to the lack of use of modern methods and means in the training curricula, especially the weighted ones, which negatively affected the achievement. The third was the methodology of the research, where the researchers used the experimental method to suit the nature of the problem. As for the research sample, they played the Diwaniyah clubs with the strong games of the long jump for the applicants and the participants in the Iraqi championships. As for the statistical methods, the researchers used the appropriate statistical means that are compatible with the research paragraphs. The results are according to a solid scientific method to reach the most important treatments and solutions, as for the mass The fifth urge was to include the most important conclusions and recommendations, as it became clear that weight training exercises an effective role on the angles of the body, the movement path, and the achievement.